Initial Evaluation on Microwave Incinerated Rice Husk Ash (MIRHA) Foamed Concrete Using Neural Network - Ridho Bayuaji (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2013)
The purpose of this study was to determine whether foamed concrete could achieve a strength requirement for structural application, while retaining its characteristics of low density, flowing workability and self-compacting. This investigation was focused on both designing compositions foamed concrete with pozzolanic material affect that has strength and density according to ASTM C 330. Neural network modelling, as observed, could enable the application of the mix proportion of foamed concrete to reach the compressive strength more than 17 MPa in which density was at 1400 kg/m3 with s/c of 0,5. 1600 kg/m3 with s/c 0,75 and 1800 kg/m3 s/c = 1. The neural networks model could be used as an alternative model in developing the tools to predicting the foamed concrete strength